THE EFFECT OF THE BARRIER-FREE NATURE, BARRIER-FREE SCIENCE EDUCATIONAL PROGRAMME ON THE ENVIRONMENTAL LITERACY LEVELS OF HEARING-IMPAIRED STUDENTS - Akgül, Hanife; Taş, Esra (Veredas do Direito, 2025)
This study aims to examine how an educational programme, which is designed to improve the creativity and learning skill levels of hearing-impaired children and partly conducted outdoors, affects their environmental literacy levels. This study was conducted using quasi-experimental design, one of the quantitative research designs. The study group consists of a total of 40 students diagnosed with hearing-impairment (20 students in the experimental group and 20 students in the control group) who were attending grades 5, 6, and 7 in formal education institutions in the central districts of Kayseri province and voluntarily participated in the project under the project criteria. The independent variable of the study was the educational programme, while the dependent variable was the environmental literacy levels of the hearing-impaired students. An educational programme that supports creativity and focuses on science for hearing-impaired children was prepared and implemented under the project, “Barrier-Free Nature, Barrier-Free Science,” with the ID No. 658976, executed by Kocasinan District Directorate of National Education and supported within the scope of TÜBİTAK 4008 - Inclusive Science and Social Practices Support Programme for Individuals with Special Needs. The data was collected using the Environmental Affect Scale. The resulting data set was analysed using the Mann-Whitney U test and the Wilcoxon Signed-Rank Test. Based on the findings, it was found that the hearing-impaired students who attended the Barrier-Free Nature, Barrier-Free Science Educational Programme had significantly higher scores on environmental affect scale compared to those who did not, and this rise was permanent.